Evidence for the agricultural origin of resistance to multiple antimicrobials in Aspergillus fumigatus, a fungal pathogen of humans. Issue 2 (13th December 2021) - Kang, S Earl; Sumabat, Leilani G; Melie, Tina; Mangum, Brandon; Momany, Michelle; Brewer, Marin T
Abstract: Pathogen resistance to clinical antimicrobial agents is an urgent problem. The fungus Aspergillus fumigatus causes 300, 000 life-threatening infections in susceptible humans annually. Azoles, which are widely used in both clinical and agricultural settings, are currently the most effective treatment, but resistance to clinical azoles is emerging worldwide. Here, we report the isolation and analysis of azole-sensitive and azole-resistant A. fumigatus from agricultural environments in the southeastern United States (USA) and show that the USA pan-azole-resistant isolates form a clade with pan-azole-resistant isolates from the United Kingdom, the Netherlands, and India. We show that several pan-azole-resistant isolates from agricultural settings in the USA and India also carry alleles with mutations conferring resistance to agricultural fungicides from the benzimidazole (MBC) and quinone outside inhibitor (QoI) classes. We further show that pan-azole-resistant A. fumigatus isolates from patients in clinical settings in the USA, India, and the Netherlands also carry alleles conferring resistance to MBC and QoI agricultural fungicides. The presence of markers for resistance to agricultural-use fungicides in clinical A. fumigatus isolates is strong evidence for an agricultural origin of pan-azole resistance in patients. The presence of multiple fungicide-resistance alleles in agricultural and clinical isolates further suggests that the unique genetics of the pan-azole-resistant clade enables the evolution and/or persistence of antimicrobial resistance mutations leading to the establishment of multifungicide-resistant isolates.